Effect of dietary supplementation of premix (vitamins and minerals) with local probiotics in different concentrations on productive performance of some local fish species 1-CyprinuscarpioL - AL-Kaabi, K. M; Mohammed, S. D; Humadi, A. J; Fahdel, A. A; Ruhayj, A. M (Journal of Madenat Alelem University College, 2015)
Several concentration of local probiotic with premix(mixed of vitamins & minerals)as a dietary supplementation in fish rations T1 (0.5%)T2(1% )T3(1.5%)T3( 2%) besides T5 (as control).Results showed that there were a significant differences between treatments (P˂0.05) T1 and T2 appeared the best performance in biological parameters (weight gain, weight rate)food conversion efficiency, blood characteristics. Results also appeared that (all probiotic and premix treatments) affected positively in fish productive performance compared with control treatment in all of parameters. As a conclusion, using of premix with probiotics improved the fish rations besides the rising of fish productive performance which due to decreasing the costs of project with gaining high fish weights.